2023
DOI: 10.1108/ijbm-09-2022-0406
|View full text |Cite
|
Sign up to set email alerts
|

Mobile payment use and payment satisfaction: mediation and moderation analyses

Abstract: PurposeWith the development of financial technology (FinTech), this paper aims to investigate the association between mobile payment use and payment satisfaction using data from the 2017 China Household Finance Survey (CHFS).Design/methodology/approachThis study uses ordered probit regressions to examine the association between mobile payments and payment satisfaction because the dependent variable is ordinal. To alleviate endogeneity problems, this study uses instrument variables and Heckman's two-step estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…First, a study by Li et al (2021) focused on customer satisfaction with bank services and established that service quality affects customer satisfaction, which consequently explains consumers' intentions to continue using such services. Similar findings on traditional banks Factors underpinning consumers ' loyalty were also found by Mainardes and Freitas (2023) and by Chen et al (2023) in the context of mobile payments. Second, in the domain of digital banks, comparable findings were also reported by Shin (2021), who found that customer satisfaction mediated the relationship between consumers' experiences with those banks' customer service and their willingness to utilize those services again.…”
Section: 38supporting
confidence: 79%
“…First, a study by Li et al (2021) focused on customer satisfaction with bank services and established that service quality affects customer satisfaction, which consequently explains consumers' intentions to continue using such services. Similar findings on traditional banks Factors underpinning consumers ' loyalty were also found by Mainardes and Freitas (2023) and by Chen et al (2023) in the context of mobile payments. Second, in the domain of digital banks, comparable findings were also reported by Shin (2021), who found that customer satisfaction mediated the relationship between consumers' experiences with those banks' customer service and their willingness to utilize those services again.…”
Section: 38supporting
confidence: 79%
“…Mobile payment refers to a transactional method wherein a mobile device is utilized to initiate, authenticate, and finalize a financial transaction involving the purchase or exchange of goods and services (Zhang et al 2023). It stands as a prominent component of mobile commerce (Chen et al 2023) and represents the natural progression of online payment systems (Alrawad et al 2023). Operating through mobile networks, this payment method leverages wireless Internet technology to process financial transactions, and devices such as smartphones, personal digital assistants, or tablets are commonly used for mobile payment transactions (Tang and Tsai 2024).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies also emphasize the vulnerability of personal and sensitive data during mobile transactions. The risk of data breaches and subsequent misuse of personal and financial data are substantial concerns in mobile payment security (Tran, 2020;Chen et al, 2023).…”
Section: Problems Outlined In Current Researchmentioning
confidence: 99%